Stosunki polsko-niemieckie na tle budowy Gazociągu Północnego (2005–2009) - Bielawska, Agnieszka (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
The paper analyzes the impact of the Nord Stream pipeline construction on Polish-German relations from 2005 to 2009. The author notes that the difficulties in reaching a consensus were further increased by the different attitudes of both governments to this investment as well as to the cooperation with Russia. From the beginning, Chancellor Gerhard Schröder was an advocate of the pipeline construction and a great promoter of German-Russian friendship, an attitude to a somewhat lesser degree also continued by his successor – Angela Merkel. Polish President Lech Kaczynski was consistently against the pipeline, supported by subsequent Prime Ministers of Poland. The Polish side was also against the tightened relations between Germany and the European Union and Russia that were supposed to ensure energy security. German visits and words of assurance, that were so numerous in the period 2004–2009, were intended to appease Warsaw but they did not mark a change of policy. Although the German government was trying to persuade Poland to support the project, Poland was consistent in its refusal to take part in it. Poland’s persistent standpoint has not changed the German attitude in this matter, while the extremely different approaches of both governments have adversely affected Polish-German relations. It was only after the Polish side ceased its continuous criticism of the pipeline project in late 2008 that a clear détente was apparent.